Critical Care and Postoperative Management of the First Human Long Segment Orthotopic Tracheal Transplantation. (1st December 2022) - Chopra, Aparna; Oropello, John M.; Wang, Jennifer; Mo, Edwin; Kohli-Seth, Roopa; Genden, Eric M.
Abstract : OBJECTIVES: To outline the postoperative management of a long segment tracheal transplant in the ICU setting. DESIGN: The recipient required reconstruction of a long segment tracheal defect from a previous prolonged intubation. A male donor was chosen for a female recipient to enable analysis of the reepithelialization kinetics using fluorescence in situ hybridization to analyze the source of the new ciliated epithelium. SETTING: Transplant ICU at the Mount Sinai Hospital, New York, NY. PATIENTS: The female recipient was previously intubated for an asthma exacerbation and subsequently developed long segment tracheal stenosis and failed conventional management including dilatation, stenting, and six major surgical procedures rendering her chronically tracheostomy-dependent. The male donor suffered a massive subarachnoid hemorrhage and was subsequently pronounced brain dead. Organ procurement occurred after obtaining appropriate consent from the patient's family. INTERVENTIONS: The patient received a deceased donor tracheal allograft that included the thyroid gland, parathyroid glands, and the muscularis of the cervical and thoracic esophagus. Triple therapy immunosuppression (tacrolimus, mycophenolate mofetil, and a corticosteroid taper) was maintained. MEASUREMENTS AND MAIN RESULTS: The patient was initially managed postoperatively with deep sedation on ventilator via armored/reinforced endotracheal tube placed through a small tracheostomy located along the superior tracheal anastomosis. Serial bronchoscopies were performed for graft assessment, pulmonary toilet, and biopsies, which initially showed acute inflammatory changes but no features of acute allograft rejection. A euthyroid state was maintained but hypercalcemia developed. CONCLUSIONS: The ICU management of this first long segment orthotopic tracheal transplant required a multidisciplinary approach involving critical care, otolaryngology, transplant surgery, interventional pulmonary, endocrinology, 1:1 nursing throughout the recipient's transplant ICU stay, and respiratory therapy that resulted in the successful establishment of a viable tracheal airway and heralded the end of chronic tracheostomy dependence.